Credit Market Imperfections, Selection, and the Distribution of Within-industry Productivity - Christian Bauer (Verein für Socialpolitik, 2010)
Recent empirical research relates lower aggregate total factor productivity to more dispersed productivity levels within narrowly defined industries. This paper shows that specificity in creditor-borrower relationships will cause adverse selection in line with this evidence. It demonstrates how more severe credit market imperfections will allow less productive firms to enter and will simultaneously prevent more productive firms from entry. To this end, I introduce endogenous credit search frictions in the spirit of Diamond (1990) in a heterogenous firm model à la Hopenhayn (1992) and Melitz (2003). In a perfect credit market, financiers can cherry-pick the most profitable firms. With credit search frictions, financiers also invest in less productive firms because this makes them better off than continuing to search for a more profitable investment opportunity. Consequently, productivity dispersion increases and average productivity falls. I use the framework to assess the impact of product market competition, more efficient credit matching, and changes in the relative bargaining power of firms and banks on productivity.
Keywords: L11; L16; O57; 330; Credit Search; Heterogenous Firms; Productivity